Cystophora cristata - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Cystophora cristata (Erxleben 1777) [Phoca] cristata Erxleben 1777, Systema Regni Animalis, Vol. 1: 590. Type Locality: "Habitat in Groenlandia australiori et Newfoundland". [S Greenland and Newfoundland]. Vernacular Names: Hooded Seal. Synonyms: Cystophora borealis Nilsson 1820; Cystophora cristata Nilsson 1841; Cystophora cucullata (Boddaert 1785); Cystophora isidorei (Lesson 1843); Cystophora leucopla (Thienemann 1824); Cystophora mitrata (G.[Baron] Cuvier 1823). Distribution: N Atlantic and Arctic ocean coastal regions of Canada (Newfoundland), Denmark (vagrant), France (vagrant), Great Britain (vagrant), Greenland, Iceland, Portugal (vagrant), Puerto Rico (vagrant), Russia (Svalbard and Novaya Zemlya), Spain (vagrant), USA (vagrant: California and Florida), Virgin Isls (vagrant). Conservation: IUCN – Lower Risk (lc). Discussion: Reviewed by Kovacs and Lavigne (1986) who placed it in subfamily Phocinae. Synonyms allocated according to Ellerman and Morrison-Scott (1951) and Kovacs and Lavigne (1986). No subspecies are recognized. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 595, DOI: 10.5281/zenodo.7316519